2007
DOI: 10.1143/jjap.46.l142
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Structure Dependence of Acid Generation in Chemically Amplified Extreme Ultraviolet Resists

Abstract: For chemically amplified photoresists, the increase in the absorption of incident radiation by polymers leads to a decrease in the absorption by acid generators. Therefore, the absorption by polymers generally degrades resist sensitivities. However, this is not true for chemically amplified electron-beam (EB) resists because of the difference in the sensitization mechanisms of the acid generators. Whether the reaction mechanism of extreme-ultraviolet (EUV) resists is analogous to that of photoresists or EB res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 24 publications
0
61
0
Order By: Relevance
“…This electron is then trapped by PAG through reductive electron transfer and activates PAG to generate acid. It has been reported that acid generation yield under EUV exposure is strongly affected by polymer structure [27][28][29][30][31]. PAG structure [32][33][34] and its loadings [33,34], respectively.…”
Section: El (%)mentioning
confidence: 99%
“…This electron is then trapped by PAG through reductive electron transfer and activates PAG to generate acid. It has been reported that acid generation yield under EUV exposure is strongly affected by polymer structure [27][28][29][30][31]. PAG structure [32][33][34] and its loadings [33,34], respectively.…”
Section: El (%)mentioning
confidence: 99%
“…Sensitization mechanism of EUV resist has been well investigated by many researchers [30][31][32][33][34][35][36][37][38][39][40]. Absorption of high-energy EUV light (13.5 nm) mainly by polymer is the first step of EUV sensitization.…”
Section: Noise Mitigation Approach (1): Dissolution Uniformity Of Nbamentioning
confidence: 99%
“…This electron is then trapped by PAG through reductive electron transfer and activates PAG to generate acid. It has been reported that acid generation yield under EUV exposure is strongly affected by polymer structure [32][33][34][35][36], PAG structure [37][38][39], and its loadings [38][39][40], respectively.…”
Section: Noise Mitigation Approach (1): Dissolution Uniformity Of Nbamentioning
confidence: 99%
“…[4][5][6]9] The acid generation mechanism for EUV resists is analogous to that of EB resists. [7][8][9] However, the absorption of incident EUV photon conforms to Lambert's Law in EUV resists as well as KrF and ArF photoresists. Thus, it is clarified that EUV resists have some similarity to those in both photoresists and EB resists.…”
Section: Introductionmentioning
confidence: 99%